Anodic lithium ion battery material with negative thermal expansion. Issue 11 (1st August 2020) - Ge, Xianghong; Yuan, Baohe; Xu, Sen; Xu, Peng; Shi, Yeping; Liu, Yanyan; Li, Zhongshuang; Sun, Qiang; Guo, Juan; Liang, Erjun; Li, Baojun
Abstract: Negative thermal expansion materials will effectively counteract possible severe expansion and contraction due to the insertion and extraction of Li ions in lithium ion batteries. Herein, negative thermal expansion ZrScMo2 VO12 and its carbon-coating composites are prepared as electrode material in lithium ion batteries by a heating treatment route. The galvanostatic charge/discharge process, cyclic voltammetry measurement and electrochemical impedance spectroscopy are tested to relate their thermal expansion and electrochemical properties. The initial specific capacity reaching 1062 mA h g -1 at the current density of 0.2 A g -1 is obtained with ideal negative thermal expansion properties. The reversible specific capacity still remains stable at 310 mA h g -1 for that material coated with carbon after 100 cycles. The corresponding theoretical simulations and in situ XRD patterns propose a Li ion storage mechanism based on Li ion insertion process in open framework structure. As a proof-of-concept research, this work paves a way to the promising application of negative thermal expansion materials in lithium ion batteries and other energy storage systems.